2007
DOI: 10.5483/bmbrep.2007.40.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Selected Non-coding Chloroplast DNA Sequences for Lineage Assessment of Musa Interspecific Hybrids

Abstract: Single-copy chloroplast loci are used widely to infer phylogenetic relationship at different taxonomic levels among various groups of plants. To test the utility of chloroplast loci and to provide additional data applicable to hybrid evolution in Musa, we sequenced two introns, rpl16 and ndhA, and two intergenic spacers, psaA-ycf3 and petA-psbJ-psbL-psbF and combined these data. Using these four regions, Musa acuminata Colla (A)- and M. balbisiana Colla (B)-containing genomes were clearly distinguished. Some t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
3
18
0
2
Order By: Relevance
“…However, only one indel at the 5′ end of petA-psbJ was able to further differentiate K. laotica and K. larsenii (excluding TT16540). This indel seems to be a part of the inverted repeat of the stem-loop or hairpin structures commonly found in angiosperms (Kim and Lee, 2004), including Zingiberales (Swangpol et al, 2007). However, external morphology of leaves can be used to unambiguously differentiate K. larsenii and K. laotica.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one indel at the 5′ end of petA-psbJ was able to further differentiate K. laotica and K. larsenii (excluding TT16540). This indel seems to be a part of the inverted repeat of the stem-loop or hairpin structures commonly found in angiosperms (Kim and Lee, 2004), including Zingiberales (Swangpol et al, 2007). However, external morphology of leaves can be used to unambiguously differentiate K. larsenii and K. laotica.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies molecular markers were identified for banana classification (Wong et al 2002;Buhariwalla et al 2005;Santos et al 2005;Ruangsuttapha et al 2007;Swangpol et al 2007;Miller et al 2008), but the usefulness of these markers depends on (a) the distribution pattern of the markers on the chromosomes; (b) the genetic and structural location of these markers on conserved regions of different genomes; and (c) the possibility of chromosomal rearrangements between potential crossing parents in the chromosome regions of economically important traits (Pillay et al 2004). In order to determine small chromosomal rearrangements such as translocations and inversions or even the position of a smaller DNA sequence a more refined methodology based on single copy fluorescent in situ hybridization (FISH) is required.…”
Section: Introductionmentioning
confidence: 99%
“…Klutuk' and 'Pisang batu') intermingled with BBs of South Asian origin. Although genetic diversity within M. balbisiana has been reported (Ude et al 2002;Ge et al 2005;Swangpol et al 2007;Wang et al 2007), it is believed that the ITC collection does not cover enough balbisiana diversity to trace the ancestral lineages of triploid cultivars comprising the B-genome (Hippolyte et al 2012).…”
Section: Wild Musa Species Diversitymentioning
confidence: 99%